Monotonicity based imaging method for time-domain eddy current problems*This paper is dedicated to Professor Guglielmo Rubinacci on the occasion of his 65th Birthday. (13th November 2017) - Su, Z; Ventre, S; Udpa, L; Tamburrino, A
Abstract: Eddy current imaging is an example of inverse problem in nondestructive evaluation for detecting anomalies in conducting materials. This paper introduces the concept of time constants and associated natural modes in eddy current imaging. The monotonicity of time constants is then described and applied to develop a non-iterative imaging method. The proposed imaging method has a low computational cost which makes it suitable for real-time operations. Full 3D numerical examples prove the effectiveness of the method in realistic scenarios.